2018
DOI: 10.1097/mat.0000000000000763
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Outcomes of Postoperative Atrial Fibrillation After Left Ventricular Assist Device

Abstract: This study sought to determine the incidence, predictors, and outcomes of postoperative atrial fibrillation (POAF) in patients undergoing implantation of left ventricular assist devices (LVADs). A retrospective analysis of all patients who underwent LVAD implantation from 2013 to 2014 was conducted. Postoperative AF, survival, and thrombotic complications were evaluated after surgery. A total of 47 patients (mean age, 56.4 ± 12.5 years; 33 male) were included and followed for a median of 331 days. Within 30 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…Deshmukh et al later published another retrospective study exclusively on 47 patients who underwent LVAD implantation and developed de novo POAF. 26 This study reported 28% incidence of de novo POAF with a median onset of 6 days after the surgery, which found no significant association between de novo POAF and mortality risk. However, it was a predicting factor for recurrent atrial fibrillation, device thrombosis, and stroke during longterm follow-up.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Deshmukh et al later published another retrospective study exclusively on 47 patients who underwent LVAD implantation and developed de novo POAF. 26 This study reported 28% incidence of de novo POAF with a median onset of 6 days after the surgery, which found no significant association between de novo POAF and mortality risk. However, it was a predicting factor for recurrent atrial fibrillation, device thrombosis, and stroke during longterm follow-up.…”
Section: Discussionmentioning
confidence: 60%
“…Thirty‐seven patients developed de novo POAF which was accounting for 20.7% of patients with no history of AF. Deshmukh et al later published another retrospective study exclusively on 47 patients who underwent LVAD implantation and developed de novo POAF . This study reported 28% incidence of de novo POAF with a median onset of 6 days after the surgery, which found no significant association between de novo POAF and mortality risk.…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of new onset atrial arrhythmias after LVAD is high in both the early postoperative period and afterward. Atrial fibrillation is documented in about 8% of patients after the first 30 days of LVAD [6,9,10]. Approximately 10-20% of patients develop new onset atrial fibrillation in the year following LVAD implant [5,6,7 ■ ,8].…”
Section: Postleft Ventricular Assist Devices Incidence Of Atrial Arrhythmiasmentioning
confidence: 99%
“…It is important to define the clinical characteristic, predictors, and treatment outcome in this population. Recent studies have shown that atrial arrhythmias, particularly atrial fibrillation, are highly prevalent in patients with advanced HFrEF before or after the LVAD implantation [1,2 ■■ ,3-6,7 ■ , 8,9]. Atrial arrhythmias have significant clinical and therapeutic implications in this population.…”
Section: Introductionmentioning
confidence: 99%
“…New-onset atrial fibrillation (AF) is prevalent among patients with left ventricular assist device (LVAD) implantation. [ 1 ] Although the clinical impact of atrial arrhythmias (AA) on LVAD recipients is not entirely clear, sustained AAs predispose patients to a risk of right heart failure. [ 2 ] Several studies have shown that AAs in LVAD support are associated with increased readmission and mortality rates.…”
Section: Introductionmentioning
confidence: 99%